Leachate treatment by using composite coagulant made from polyaluminium chloride (PAC) and tapioca starch (TS) - Omar, Mohamad Azizan (2019)
Landfill leachate is considered as the highly polluted liquid that is produced from infiltration of water through municipal solid waste. Coagulation and flocculation are commonly used in the leachate treatment. This study investigates the effectiveness of composite coagulant PACTS made from polyaluminum chloride (PAC) and tapioca starch (TS) in the removal of colour, turbidity, suspended solids (SS), chemical oxygen demand (COD) and ammonia from Simpang Renggam landfill. PAC was selected as a primary coagulant since it has superiority at a lower dosage and applicable at wider pH value compare to other chemical coagulants. While, TS as a natural coagulant is available in abundance, cheaper, environmentally friendly and has ability to improve the coagulation efficiency. A series of jar test were carried out to determine pH and dose for single, dual and composite coagulants. From the result analysis, the highest percentage removal of PAC at optimum condition as single coagulant (dose 2.5 g/L at pH 7) in term of SS, turbidity, colour, COD and ammonia were 92%, 77%, 94%, 37% and 32 %, respectively. Whereas TS coagulant, at optimum condition (dose 2.5 g/L at pH 8) shows 35%, 13%, 30%, 0% and 38% removals correspondingly. Also, in dual coagulants, the percentage removal of suspended solids, turbidity, colour, COD and ammonia of dual coagulant (dose PAC 1.5 g/L and dose TS 0.2g/L at pH 5) was 90%, 74%, 87%, 40% and 17% in that order. Furthermore, under the composite coagulant method, the PACTSb with dose 1.5 g/L at pH 5 was selected as an optimum ratio, dose and pH for composite coagulant. The percentage removal as regards SS, turbidity, colour, COD and ammonia (98%, 83%, 86%, 46% and 28%) increased when compared with a single and dual coagulant methods. These are indications that the combination of chemical coagulant (PAC) and natural coagulant (TS) as a composite coagulant was able to combine the best properties of both coagulants and increase the coagulation efficiency.